Pengetahuan dan Sikap Ibu Terhadap Pemberian Makanan Lengkap - Pekabanda, Kartini; Toru, Veronika; Mila, Antonetha R H (Poltekkes Kemenkes Kupang, 2023)
Background: Introduction: Stunting has a negative impact in the short term, namely causing impaired brain development, intelligence, impaired physical growth, and metabolic disorders in the body. The long-term adverse effects that can be caused are decreased cognitive abilities and learning achievement, decreased immunity so that it is easy to get sick, and a high risk of degenerative diseases in old age. Objective: This study aims to analyze the relationship between knowledge and maternal attitudes towards the Accuracy of Providing Complementary Feeding. Method: The sampling technique used in this study was accidental sampling. The subjects of the study were 44 mothers who had babies who came for check-ups at the health center. Bivariable analysis with the Chi Square test. Results: Showed that 35.7% of mothers did not provide appropriate complementary feeding. 18% had a low level of knowledge about the accuracy of providing complementary feeding, 16% of respondents had a low attitude about the accuracy of providing complementary feeding. There is a positive relationship between maternal knowledge (p = 0.001) and maternal attitudes (p = 0.001) with the accuracy of providing complementary feeding at the Kambaniru Health Center, East Sumba Regency.